2019
DOI: 10.1021/acs.langmuir.9b01078
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Assembly of Class II Hydrophobins from T. reesei at the Air–Water Interface

Abstract: Class II hydrophobins are amphiphilic proteins produced by filamentous fungi. One of their typical features is the tendency to accumulate at the interface between an aqueous phase and a hydrophobic phase, such as the air−water interface. The kinetics of the interfacial self-assembly of wild-type hydrophobins HFBI and HFBII and some of their engineered variants at the air− water interface were measured by monitoring the accumulated mass at the interface via nondestructive ellipsometry measurements. The resultin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 54 publications
(81 reference statements)
0
9
0
Order By: Relevance
“…This stock solution was diluted to a concentration of 4 μM for further use. At this concentration, the droplets (radii: 0.52–0.62 mm) contain almost double the amount of proteins needed for full surface coverage of 0.45 μmol/m 2 . The dilution was performed by the addition of either a 10 mM acetate buffer with an ionic strength of 6 mM for the droplets with low salt concentrations or the same buffer supplemented with KCl to obtain an ionic strength of 954 mM for the droplets with high salt concentration.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This stock solution was diluted to a concentration of 4 μM for further use. At this concentration, the droplets (radii: 0.52–0.62 mm) contain almost double the amount of proteins needed for full surface coverage of 0.45 μmol/m 2 . The dilution was performed by the addition of either a 10 mM acetate buffer with an ionic strength of 6 mM for the droplets with low salt concentrations or the same buffer supplemented with KCl to obtain an ionic strength of 954 mM for the droplets with high salt concentration.…”
Section: Methodsmentioning
confidence: 99%
“…The bilayer formation for the water permeability measurements were oriented on the so-called “DIB” method (droplet interface bilayer , ), which was previously used to calculate the permeability of lipid bilayers. ,, Therefore, small droplets (radii: 0.52–0.62 mm) of aqueous solution were formed in oil. After a relaxation time of at least 30 min, during which the molecules were allowed to adsorb at the interface of the droplets and form a dense monolayer, two droplets with different osmotic concentrations were brought into contact with a metal needle to form a bilayer. The contact area formed in this way has already been shown to be a protein bilayer and is impermeable to ions, as shown by measurements of the layer thickness and voltage-clamped membrane current …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 1 ] Therefore, controlling the physical and chemical properties of interfaces is of fundamental importance in different materials such as foams, emulsions, and proteins and nanoparticle self‐assembly. [ 2,3,4 ]…”
Section: Introductionmentioning
confidence: 99%
“…(1,2) The superior surface elasticity of hydrophobin films (5,6) originates from the ordered self-assembled structure at fluid interfaces. (7)(8)(9)(10)(11) This property has recently been utilized in bilayer studies of hydrophobin films by microfluidic approach, (12) where bilayers' adhesion energy was determined. Also the pH of the surroundings plays a role, it has been shown that changes in pH alter the structure and elasticity of the hydrophobin film by reorienting hydrophobin molecules and subsequently affecting the interaction between the hydrophobins at the air-water interface.…”
Section: Introductionmentioning
confidence: 99%